2014
DOI: 10.1002/anie.201403778
|View full text |Cite
|
Sign up to set email alerts
|

Anion‐Binding Catalysis by Electron‐Deficient Pyridinium Cations

Abstract: A new activation principle in organocatalysis is presented: halide binding through Coulombic interactions. This mode of catalysis was realized by using 3,5-di(carbomethoxy)pyridinium ions that carry an additional electron-withdrawing substituent on the nitrogen atom, for example, pentafluorobenzyl or cyanomethyl. For the N-pentafluorobenzyl derivative, Coulombic interaction with the pyridinium moiety is complemented in the solid state by anion-π interactions with the perfluorophenyl ring. Bromide and chloride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 39 publications
6
58
0
4
Order By: Relevance
“…Berkessel et al 105 developed a series of electron-poor 3,5-dicarbomethoxypyridinium tetraphenylborate salts 237a-237d as an anion-binding catalyst, directed via Coulombic interactions. Proton NMR titration studies of 237a with tetrabutylammonium chloride in THF-d 8 /CD 3 CN (9:1, v/v) demonstrated a thermodynamic preference for chloride over BPh 4 À , with a derived association constant of 200 M À1 .…”
Section: Catalysismentioning
confidence: 99%
“…Berkessel et al 105 developed a series of electron-poor 3,5-dicarbomethoxypyridinium tetraphenylborate salts 237a-237d as an anion-binding catalyst, directed via Coulombic interactions. Proton NMR titration studies of 237a with tetrabutylammonium chloride in THF-d 8 /CD 3 CN (9:1, v/v) demonstrated a thermodynamic preference for chloride over BPh 4 À , with a derived association constant of 200 M À1 .…”
Section: Catalysismentioning
confidence: 99%
“…This is remarkable for an eutral monodentate catalyst as only multidentate and/or charged hydrogen-, [27] halogen-, [28] chalcogen-bonding, [12] and coulombic [29] catalysts had proved to be proficient thus far.W ithout catalyst, product 18 was formed in only 3% yield, even after 90 hr eaction time.T ellurium catalyst 4 still gave 18 in 48 % yield (Table 1, entry 5) whereas the yield dropped to 15 %for iodopentafluorobenzene 6 (entry 6). Thel ess electron-deficient antimony catalyst 8 with one phenyl group gave ar educed yield of 30 %c ompared to catalyst 1 (entry 2).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[13] Interessanterweise erwies sich das Salz 9·Br, ohne elektronenziehende Substituenten am Pyridinring,a ls inaktiv.D iese Notwendigkeit hinreichender Elektronenarmut gleicht unseren vorherigen Beobachtungen im Falle der Silylenolether-Addition an aChlorether. [8] Nachdem die THP-Schützung erfolgreich etabliert werden konnte,w andten wir uns Glycosylierungsreaktionen zu (Tabelle 1). Dabei wurden benzyl-, silyl-und acetylgeschützte Galactale (10 a-c)u nd Glucale (11 a-c)a ls Glycal-…”
Section: Methodsunclassified
“…[8] Diese Modellreaktion wurde ursprünglich von Jacobsen et al unter Verwendung des Thioharnstoffs 3 (Schema 1a)b eschrieben. [9] Die Anwendungen von Thioharnstoffen in der Organokatalyse sind inzwischen mannigfaltig.…”
unclassified